2018
DOI: 10.1055/s-0044-101026
|View full text |Cite
|
Sign up to set email alerts
|

Gaze patterns hold key to unlocking successful search strategies and increasing polyp detection rate in colonoscopy

Abstract: This study defined distinct VGPs that are associated with expert behavior. These data may allow introduction of visual gaze training within structured training programs, and have implications for adoption in higher-level assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…27,28 In addition, visual gaze patterns differ between endoscopists, and it has been shown that endoscopists with a wider visual gaze pattern or center-looking visual gaze pattern may have a higher adenoma or polyp detection rate than endoscopists with other visual gaze patterns. 29,30 Finally, "inattentional blindness" 31,32 and "change blindness" 33 phenomena may add to intraproceduralist variability, and neither wider-viewing colonoscopes nor second observer strategies may completely address these issues. Therefore, high-performance CADe may serve as a more standardized "second eye" in assisting the endoscopist to avoid missing any lesion.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In addition, visual gaze patterns differ between endoscopists, and it has been shown that endoscopists with a wider visual gaze pattern or center-looking visual gaze pattern may have a higher adenoma or polyp detection rate than endoscopists with other visual gaze patterns. 29,30 Finally, "inattentional blindness" 31,32 and "change blindness" 33 phenomena may add to intraproceduralist variability, and neither wider-viewing colonoscopes nor second observer strategies may completely address these issues. Therefore, high-performance CADe may serve as a more standardized "second eye" in assisting the endoscopist to avoid missing any lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of better identification of any precancerous lesions during colonoscopy, tremendous efforts from both hardware engineers and clinicians have been put to make lesions more visible to the endoscopists [26], However, endoscopists still miss a large portion of precancerous lesions within the screen, for both lesions with non-obvious visual features and lesions that briefly flashed across the screen. These conditions are very challenging even for experienced endoscopists, because humans are always susceptible to "inattentional blindness", "change blindness", visual gaze pattern, fatigue, interobserver variabilities or any distractions [18,27,28,29,30,31,32]. Till now, only secondobserver strategies seem helpful to decrease the miss rate of visible polyps for low ADR detectors [26,33].…”
Section: Discussionmentioning
confidence: 99%
“…These findings showed no correlation with level of experience. 87 Visibility of colorectal lesions using WLE, BLI and LCI with an eye-tracking system was evaluated in 10 endoscopists (9 non-experts). The miss-rate was significantly lower for BLI (6%) and LCI (4.3%), respectively, than with WLE (12.6%) and significantly shorter detection time for BLI and LCI.…”
Section: Eye-trackingmentioning
confidence: 99%